2013
DOI: 10.1021/jp4053743
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Infrared Spectroscopy of Isotope-Diluted Low Density Amorphous Ice

Abstract: We present two-dimensional (2D) infrared (IR) spectra of isotope diluted ice in its low density amorphous form. Amorphous ice, which is structurally more similar to liquid water than to crystalline ice, provides higher resolution spectra of the hydrogen bond potentials because all motion is frozen. In the case of OD vibration of HOD in H2O, diagonal and off-diagonal (intermode) anharmonicity as well as the relaxation rate of the first excited state increase with hydrogen bond strength in a consistent way. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…This provides a combination of structural and temporal sensitivity. The method has been applied to neat liquid water, [31][32][33][34][35][36][37] liquid water under confined conditions, [38][39][40] water in dilute solutions, [41][42][43] amorphous ice, [44][45][46] and the supercooled state. 47 Diagonal peaks arising from exciting one vibration and probing it again at a later time reveal information about spectral diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a combination of structural and temporal sensitivity. The method has been applied to neat liquid water, [31][32][33][34][35][36][37] liquid water under confined conditions, [38][39][40] water in dilute solutions, [41][42][43] amorphous ice, [44][45][46] and the supercooled state. 47 Diagonal peaks arising from exciting one vibration and probing it again at a later time reveal information about spectral diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…23 2D IR spectroscopy 24-28 monitors the local structure and dynamics of the hydrogen bonds in water through the frequency of the hydroxyl stretch vibration. [29][30][31][32] We demonstrated that the high structural disorder of LDA on the one hand, and the complete lack of spectral diffusion on the other hand, allow one to observe how various spectral properties of the hydroxyl a) phamm@pci.uzh.ch stretch vibration varies with hydrogen bond strength to the water molecules in the first coordination shell.…”
mentioning
confidence: 99%
“…This procedure separates vibrational (anisotropic) from thermal (isotropic) signals by exploiting the lack of orientation motion in the ice samples. 23 The on-diagonal (blue) peaks are associated with bleach and stimulated emission between ground and first excited state (0-1 transition), while the oppositely signed off-diagonal peaks (red) are due to the anharmonically shifted absorption from the first to the second excited state (1-2 transition). For all three samples, the lineshapes of 0-1 transition are consistent in terms of bandwidth and position with the corresponding absorption spectra (Fig.…”
mentioning
confidence: 99%
“…This absence of spectral diffusion indicates that the environment of the tight complex is static on the timescale of typical fluctuations of this solvent and resembles that of ag lass. [15] Similarly slow spectral diffusion has only been reported for ionic liquids. [16] Asubstantial slowing down of the translational dynamics of water has also been observed in the solvation shell of different solutes.…”
Section: Angewandte Chemiementioning
confidence: 86%